Psychosocial Determinants of Financial Conduct: A Structural Mediation Analysis of Self-Esteem, Parental Authority, and Materialism - Yuniarti, Andi; Fadhillah, Prayudhi (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
This study examines how self-esteem and parental authority shape students’ financial behavior through materialistic attitudes among undergraduates at state universities in Makassar. We advance a novel mechanism by showing that psychological self-evaluation and parental control influence financial behavior primarily through the formation of materialistic preferences, rather than through direct behavioral channels. Using primary data from 200 respondents collected via online and printed questionnaires, we employ structural equation modeling (PLS-SEM) to test both direct and indirect relationships. The results indicate that self-esteem and parental authority significantly increase materialistic attitudes, while materialism exerts a negative effect on financial behavior. Direct effects of self-esteem and parental authority on financial behavior are insignificant, but both variables exert significant negative indirect effects through materialistic attitudes. These findings suggest that interventions aimed at improving student financial behavior should address underlying materialistic orientations shaped by family and psychological factors, rather than solely on financial skills or knowledge.